Keseimbangan Kehidupan Kerja Ditinjau Dari Dukungan Sosial Pada Pekerja - Retno Manggaharti; Nur Pratiwi Noviati (Faculty of Ushuluddin and Humanities, 2019)
The balance of work life in Indonesia has become an issue that has received more attention for various companies and agencies. The balance of work life is vital to be able to balance all aspects of the life of workers, both related to personal growth and work life. This study aims to examine the correlation of social support empirically and work-life balance. The more positive the support received, the higher the level of work-life balance. Respondents in this study are people who work both married and those who have not, amounting to 77 respondents. The measuring instrument used is a work-life balance scale with a Cronbach coefficient alpha and a social support scale with a Cronbach alpha coefficient. The data analysis method used is a statistical method with help with SPSS 24 for windows program facilities. Correlation test shows the results of social support and work-life balance have a correlation coefficient r of 0.730 and p = 0.001 (p <0.01). The results of the analysis show that there is a significant positive relationship between social support and work-life balance, and thus the research hypothesis is accepted